Born To Work?: An Ethnographical Picture of Child Labourers in the Rural Part of Northern Karnataka - Nanjunda, Devajana C. and Dinesha, P.T (2011)
There is no doubt that the iniquitous and exploitative nature of the economy and the socio-economic milieu lead to the harsh reality of child labour, and determine to a significant extent the working and living conditions of child workers. Children are part and parcel of the economic activity of each and every society. Notwithstanding the fact that child labour is not a new phenomenon and it has existed even in ancient times, its form has been kept changing. Poverty, population explosion, survival strategy of the poor and exploitative economic systems are regarded as the causes of child labour in India. The data of the study is focusing on nature of the work done by child labourers, their socio-economic background (such as age, level of schooling, family size, and parental education and income), earnings and difficulties faced by them as child labourers. This paper is based on the fieldwork conducted in northern Karnataka India during 2010-2011 and it discusses the various issues and the main measures government and non-government organisations can take in order to deal with the issue of child labour soon.